INTEGRASI NILAI-NILAI ISLAM DI MADRASAH ALIYAH AL-BIDAYAH - Shali Wulandari, - (2022)
The integration of general science with religious science is included in an interactive-interconnective approach, which is expected to be able to work together, and understand each other in terms of the approach and method of thinking of the two sciences. However, the integration of the two disciplines, especially those related to learning management and the readiness of school institutions, still has obstacles. For this reason, an appropriate design is needed for the integration of general subjects so that they are in accordance with the expected Islamic values. This study aims to identify related to planning, implementation, and problems faced by integrated learning of Islamic values in science and social studies cluster subjects. As an effort to synergize Islamic insight with the context of modern understanding. The participants in this research were teachers who were in charge of the science and social studies clusters for class X, XI, and XII, as well as students in class XII. This type of research used a qualitative approach with a descriptive method with the researcher as the main instrument. Collecting data using interview, observation, and documentation techniques. Data analysis techniques using rduction, data display, and verification. The results of the study indicate that the integration of Islamic values in the science and social studies clusters at Madrasah Aliyah Al-Bidayah has begun by modifying the learning components that are adapted to the school environment and student conditions. So as to make students better understand Islamic values from various scientific points of view and can apply them in everyday life.